Research and innovation in teacher’s training and the services’s coordinators for children in Italy - Cristina Stringher; Manuela Gallerani (Revista Electrónica Interuniversitaria de Formación del Profesorado)
In this article we discuss about the training of teachers and coordinators in early childhood education and care (ECEC) services in Italy. We are doing this through two parts: in the first one, after an introduction on the topic of ECEC quality, we give an account of present profiles of educators in baby centres (asili nido), educators in pre-schools and coordinators of 0-6 services; the second part presents two exemplary experiences of initial training of teachers and coordinators carried out in the Universities of Bologna and Roma-Tre. We proceed departing from critical issues emerging from the analysis of profiles.